Chronic Acquired Demyelinating Polyneuropathy following Renal Transplantation. (2nd December 2013) - Younger, D. S.; Orsher, Stuart
Abstract : The clinical, laboratory, and treatment findings of a patient with chronic acquired demyelinating polyneuropathy (CADP) in association with renal transplantation are described. Like the present case, many such patients have been described under the rubric of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP).